2005
DOI: 10.1007/s10886-005-7114-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geldanamycin on Hatching and Juvenile Motility in Caenorhabditis elegans and Heterodera glycines

Abstract: Abstract-Several Streptomyces species are known to produce metabolites that inhibit plant pathogens. One such compound is geldanamycin (GA), a benzoquinone ansamycin originally isolated from Streptomyces hygroscopicus. We examined the effect of geldanamycin on egg hatch and juvenile motility in Caenorhabditis elegans and in two populations of the plant-parasitic nematode Heterodera glycines. When C. elegans eggs were exposed to geldanamycin, both hatch and motility were reduced by GA doses between 2 and 50 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Geldanamycin, unlike the other drugs in this study, was predicted to induce a transcriptional profile opposite to that of rapamycin. Another study showed that prolonged treatment of geldanamycin had detrimental effects on motility and is hence in line with our results (Skantar et al ., 2005). Geldanamycin inhibits Hsp90, mutants of which have been shown to have muscle cell defects (Gaiser et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Geldanamycin, unlike the other drugs in this study, was predicted to induce a transcriptional profile opposite to that of rapamycin. Another study showed that prolonged treatment of geldanamycin had detrimental effects on motility and is hence in line with our results (Skantar et al ., 2005). Geldanamycin inhibits Hsp90, mutants of which have been shown to have muscle cell defects (Gaiser et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Carcasses and other debris were dissolved after 5-10 min, and resistant eggs (50% to 100% viable eggs) were collected and washed several times in an M-9 buffer [46]. The M-9 buffer was prepared with 1.5 g of KH 2 PO 4 , 3.0 g of Na 2 HPO 4 , 2.5 g of NaCl, 0.5 mL of 1 M MgSO 4 , and sterile distilled water to a final volume of 500 mL [68]. Eggs were deposit in agar plates for 48 h, and young worms (larval stage 4 and 5) were harvested and resuspended in the M-9 buffer.…”
Section: Toxicity Assaysmentioning
confidence: 99%
“…The 24-well plates were covered with transparent plastic, and incubated at 20°C for 24 h. After incubation, nematodes were counted and determined as motile or non-motile using an inverted microscope. Nematodes were considered motile when they exhibited any movement, and as non-motile when there were no tail, head, or pharyngeal movements during 5 s of observation (Skantar et al 2005). It is important to differentiate motility in adult nematodes from movement caused by larvae hatched from eggs inside the body of dead C. elegans.…”
Section: Anthelmintic Assaymentioning
confidence: 99%